Rate and Pulse Based Plasticity Governed by Local Synaptic State Variables - Mayr, Christian G.; Partzsch, Johannes (Frontiers in Synaptic Neuroscience, 2010)
Classically, action-potential-based learning paradigms such as the Bienenstock-Cooper-Munroe (BCM) rule for pulse rates or spike timing dependent plasticity (STDP) for pulse pairings have been experimentally demonstrated to evoke long-lasting synaptic weight changes (i.e. plasticity). However, several recent experiments have shown that plasticity also depends on the local dynamics at the synapse, such as membrane voltage, Calcium time course and -level, or dendritic spikes. In this paper, we introduce a formulation of the BCM rule which is based on the instantaneous postsynaptic membrane potential as well as the transmission profile of the presynaptic spike. While this rule incorporates only simple local voltage- and current dynamics and is thus neither directly rate nor timing based, it can replicate a range of experiments, such as various rate and spike pairing protocols, combinations of the two, as well as voltage-dependent plasticity. A detailed comparison of current plasticity models with respect to this range of experiments also demonstrates the efficacy of the new plasticity rule. All experiments can be replicated with a limited set of parameters, avoiding the overfitting problem of more involved plasticity rules.